Elementary number theory, group theory, and Ramanujan graphs - Davidoff, Giuliana P. (London Mathematical Society student texts, 2003)
This text is a self contained treatment of expander graphs and in particular their explicit construction. Expander graphs are both highly connected but sparse, and besides their interest within combinatorics and graph theory, they also find various applications in computer science and engineering.